Influence of Electronic Word of Mouth, Perceived Quality, and Customer Engagement on Brand Trust (Study on Generation Z Women Wardah Cosmetics Users in Surabaya) - Fikha Fitriyah; R. Yuniardi Rusdianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research was conducted to determine the effect of Electronic Word of Mouth, Perceived Quality and Customer Engagement on Brand Trust in Generation Z Female Wardah Cosmetic Users in Surabaya City. This research uses a quantitative approach. The population in thus study in Generation Z Women in Surabaya City who have purchased Wardah cosmetic. The data collection technique used a questionnaire with a sample size of 205 respondents. The data collection technique uses multiple liniear analysis. The results of this study indicate that simultaneously electronic word of mouth (X1), perceived quality (X2) and customer engagement (X3) have a positive and significant effect on brand trust. Furthermore, partially electronic word of mouth (X1), perceived quality (X2) and customer engagement (X3) have a positive and significant effect on brand trust.